2020
DOI: 10.1098/rsos.201116
|View full text |Cite
|
Sign up to set email alerts
|

A green extraction design for enhancing flavonoid compounds from Ixora javanica flowers using a deep eutectic solvent

Abstract: In this study, an environmentally friendly extraction method for flavonoid compound from Ixora javanica , as a new raw material candidate for herbal medicine and cosmetics, was developed. The objectives of the present work were to provide recommendations for the optimal extraction conditions and to investigate the effects of any extraction parameters on flavonoid yields from the I. javanica flower. The extraction process was performed using deep eutectic solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…On the other hand, as shown in Table 2, other ethnomedicinal extracts had no inhibition activity against sucrase αglucosidase. In another study, Oktaviyanti et al (2020) evaluated the total flavonoids from I. javanica whose phytochemicals, such as flavonoid glycosides and triterpenoids, have been isolated from I. javanica (Dontha et al 2015). In addition, several previous studies reported bioactivities of genus Ixora, such as anti-inflammatory, antimicrobial, antidiabetic, antiplatelet, antidiarrhea, and wound-healing potency (Maniyar et al 2010;Anila and Hashim 2019;Ragasa et al 2004).…”
Section: Antidiabetes Activitymentioning
confidence: 99%
“…On the other hand, as shown in Table 2, other ethnomedicinal extracts had no inhibition activity against sucrase αglucosidase. In another study, Oktaviyanti et al (2020) evaluated the total flavonoids from I. javanica whose phytochemicals, such as flavonoid glycosides and triterpenoids, have been isolated from I. javanica (Dontha et al 2015). In addition, several previous studies reported bioactivities of genus Ixora, such as anti-inflammatory, antimicrobial, antidiabetic, antiplatelet, antidiarrhea, and wound-healing potency (Maniyar et al 2010;Anila and Hashim 2019;Ragasa et al 2004).…”
Section: Antidiabetes Activitymentioning
confidence: 99%
“…Some experiments suggest that UAE and MAE do not improve flavonoid extraction [ 49 ], leading us believe that the most crucial aspect is the solvent used in the extraction. In this regard, it seems there is consensus that deep eutectic solvents (DES) are highly recommended to improve flavonoid extraction [ 50 ]. Moreover, these solvents can be employed to target specific flavonoids [ 51 ].…”
Section: Extraction Isolation and Characterization Of Flavonoidsmentioning
confidence: 99%
“…However, high water contents (30, 40, and 50%) can limit the interactions between the solute and solvents, and thus, lower the extraction efficiency. [60][61][62] Based on these results, NADES-12 with 20% water was used for the subsequent experiments.…”
Section: Extraction Effect Of Different Water Content In Nadesmentioning
confidence: 99%
“…However, prolonged sonication can alter or even decompose the target compounds, resulting in lower yields. 60,62,65 Thus, the targeted compounds could be completely extracted within 30 min and the condition was used for subsequent experiments.…”
Section: Extraction Effect Of Different Extraction Time Periodsmentioning
confidence: 99%